Dynamics of Islamic Unity Education Institute - Malik, Darussalam; Ansori, M. Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this study was to find out the history and dynamics of Persis educational institutions. The research method uses library research with data sources in books form and scientific journals related to the dynamics of educational institutions, and data analysis techniques use content analysis. The study results revealed that Persis birth began with a Tadarusan formation (Islamic religious study) group in Bandung city led by H. Zamzam and H. Muhammad Yunus. Persis has been led by several figures who have their own characteristics of thought, including KH. Zamzam as Persis founder. Ahmad Hasan is the main teacher and founder of Persis. Mohammad Natsir is a political scholar. KH. E. Abdurrahman was a great scholar and a humble legal expert. Persis gives great attention to the education field. In this education field, Persis has established educational institutions ranging from early childhood or kindergarten to tertiary institutions, both in madrasas form, schools, and Islamic boarding schools. Apart from that, Persis also organizes courses and discussion groups. So it is necessary to continue to maintain this spirit, especially in eradicating stupidity context, backwardness, superstition, heresy, and superstition, as well as Indonesian people colonization by carrying out enlightenment among Muslims.